Black entrepreneurship and ethnic beauty salons: Possibilities for Resistance in the Social (Re)Construction of the Black Identity - Rezende, Ana Flávia; Mafra, Flávia Luciana Naves; Pereira, Jussara Jessica (Organizações & Sociedade, 2018)
This paper addresses the case of five black entrepreneurs who own businesses dealing with a public that for years has denied its aesthetic and phenotypic traits. These spaces, branded as ‘ethnic salons’, aim to take care of the curly and / or Afro hair of Black men and women. In the face of this context, we ask: how can Black entrepreneurs and enterprises, confront colonial mentality in social relations, by creating businesses aimed at giving value to, and appreciating the identity of Black men and women? The field research was conducted via observations and interviews, collecting narratives from both. The narratives went through synthesis and analysis processes that allowed us to flag the motives behind these enterprises, as well as the racial/ethnic acceptance present in these spaces. Thus, the main contribution of this paper is to discuss ‘hair type’ as a constitutive element of Black racial identity, and the opportunity for more autonomy when entering the labor market.